2012
DOI: 10.1080/17523281.2012.703224
|View full text |Cite
|
Sign up to set email alerts
|

Use and abuse: understanding the intersections of childhood abuse, alcohol and drug use and mental health

Abstract: It is well recognized that there is a relationship between child abuse, mental illness, and alcohol and drug abuse. This article reports on the findings of a qualitative research project exploring the experiences of adult survivors of child abuse in alcohol and other drugs (AOD) services, as well as the experiences of AOD workers with this client group. The project complements existing research on the relationship between child abuse, AOD use and adult mental health; however, it uniquely explores these issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…A number of themes relating specifically to AOD treatment and practice have been explored in previous publications (Breckenridge & Salter, ; Breckenridge, Salter, & Shaw, ). However, the study identified a broader set of issues about the linkages between the prevailing paradigms of drug and criminal justice policy and the politics of AOD treatment, and the particular location of female clients within this complex interplay of ideology and practice.…”
Section: Methodsmentioning
confidence: 99%
“…A number of themes relating specifically to AOD treatment and practice have been explored in previous publications (Breckenridge & Salter, ; Breckenridge, Salter, & Shaw, ). However, the study identified a broader set of issues about the linkages between the prevailing paradigms of drug and criminal justice policy and the politics of AOD treatment, and the particular location of female clients within this complex interplay of ideology and practice.…”
Section: Methodsmentioning
confidence: 99%
“…Outra característica relacionada ao agressor, mesmo com muitos protocolos sem informação, refere-se ao uso de álcool ou de outras drogas ilícitas. A associação entre uso ou abuso de álcool e outras drogas e a prática da violência doméstica foi encontrada por outras pesquisas 15,16,18 , e esses dados apontam para a necessidade de se investir em políticas de prevenção e tratamento aos dependentes químicos, como uma forma de prevenir também os maus-tratos, pois o abuso de substâncias figura como um importante fator desencadeante ou facilitador desse tipo de violência.…”
Section: ▄ Discussãounclassified
“…Contudo, no que se refere à violência física e à negligência, a mãe figura como a principal responsável pelos maus-tratos. As pesquisas também evidenciam uma correlação positiva entre a perpetração da violência doméstica e o abuso de álcool ou de outras drogas, visto que muitas famílias vivem sob condições socioeconômicas desfavoráveis 1,[10][11][12][13][14][15][16][17][18][19] .…”
Section: ▄ Introduçãounclassified
“…For example, many family violence refuges will not admit women with active AOD problems (Humphreys et al 2005;Braaf 2012;Macy and Goodbourn 2012), and women who experience cooccurring DFV and substance abuse issues are less likely to complete treatment programs (Noonan et al 2017). A further barrier is that many AOD services are not childfriendlyif they admit children at alland may even see children as impediments to a woman's recovery (Breckenridge et al 2012;Salter and Breckenridge 2014). However, there may be nowhere else for the children to go; women are understandably reluctant to leave their children with violent partners while they attend detox or rehabilitation services, and may fear having their children removed by statutory authorities if they disclose substance abuse issues to government agencies (Bennett and Bland 2008).…”
Section: Aod As a Coping Mechanismmentioning
confidence: 99%